2005
DOI: 10.1124/jpet.105.090837
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Phosphodiesterase-4 Ameliorates Chronic Colitis and Prevents Intestinal Fibrosis

Abstract: The phosphodiesterase-4 (PDE4) inhibitors may be an important target in the treatment of several inflammatory conditions. The anti-inflammatory effect of PDE4 inhibitors bears similarities with that of steroids, without interfering with the hypophysary-adrenal-axis. We compared the effect of rolipram, a selective PDE4 inhibitor, with steroids on the clinical course of experimental colitis induced by 2,4,6-trinitrobenzenesulfonic acid (TNBS). Three groups of rats (n ϭ 20) received TNBS. One group received methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…The TNBS-induced increase in MPO activity was reduced by approximately 60% in mice receiving daily doses of ABC294640. As anticipated from the literature (Videla et al 2006), prednisolone also suppressed neutrophil accumulation in the colon. Variability did not allow any changes to reach statistical significance.…”
Section: Mouse Tnbs Modelsupporting
confidence: 52%
“…The TNBS-induced increase in MPO activity was reduced by approximately 60% in mice receiving daily doses of ABC294640. As anticipated from the literature (Videla et al 2006), prednisolone also suppressed neutrophil accumulation in the colon. Variability did not allow any changes to reach statistical significance.…”
Section: Mouse Tnbs Modelsupporting
confidence: 52%
“…Videla et al 45 reported that rolipram ameliorated intestinal fibrosis by downregulating TGF-␤1. Sanz et al 46 demonstrated that roflumilast inhibited leukocyte-endothelial cells interaction.…”
Section: Discussionmentioning
confidence: 98%
“…In any event, the effects of PDE4 inhibition on reducing stressinduced colonic evacuation have clearly been demonstrated for the first time in the present studies. [48] . Previous studies in this model have demonstrated that the increased stress-induced defecation is associated with increased colonic transit/evacuation [13] , and available literature has demonstrated PDE inhibition can act to decrease colonic motility and increase intestinal secretion.…”
Section: Discussionmentioning
confidence: 99%